Pengembangan Multimedia Pembelajaran Pada Mata Pelajaran Dasar Usaha Layanan Parawisata (DULP) di Kelas X SMKN 2 Kota Padang - Ivandri Ravayadi; Rahmi, Ulfia (Jurnal Family Education, 2024)
The objective of this research was to create a viable and practical multimedia learning product for class X DULP SMKN 2 Padang City that fulfils the criteria of material and media feasibility. This study employs the ADDIE paradigm, including the phases of Analysis, Design, Development, Implementation, and Evaluation, within the domain of research and development. The research participants included individuals with expertise in media, materials, learning, as well as teachers and students. The study approach included questionnaire tools and evaluation sheets. The used data analysis technique included both quantitative and qualitative analytical methodologies. The validator performed a product validity assessment on the material component and achieved an average score of 4.88, indicating a high degree of validity. The media components evaluated by the validator achieved an average score of 4.64, indicating a substantial degree of validity. Validator II achieved a mean score of 4.73, indicating a substantial degree of validity. Moreover, the evaluation of the feasibility of multimedia learning, based on the performed trials, yielded an average score of 4.67, indicating a noteworthy degree of practicality. The evaluation of the effectiveness of using multimedia yielded an average score of 85% and a completion rate of 90%, classifying it as "Highly Effective". Investigation into the development of educational multimedia for classroom instruction The study results suggest that incorporating multimedia into DULP courses is very effective in enhancing the learning process.